Up to what point is loss reduction environmentally friendly?: The LCA of loss reduction scenarios in drinking water networks. (1st November 2016) - Pillot, Julie; Catel, Laureline; Renaud, Eddy; Augeard, Bénédicte; Roux, Philippe
Abstract: In a context of increasing water shortage all over the world, water utilities must minimise losses in their distribution networks and draw up water loss reduction action plans. While leak reduction is clearly an important part of sustainable water management, its impacts have to be reconsidered in a broader objective of environmental protection than strictly the avoided losses in cubic metres of water. Reducing the volume of water abstracted reduces also environmental impacts associated to water production (the operation and infrastructure needed for abstraction, treatment, supply). In the mean time, activities for reducing water losses generate their own environmental impacts, notably as a result of the work, equipment, and infrastructures used for this purpose. In this study, Life Cycle Assessment (LCA) was used to assess and compare two sets of environmental impacts: those resulting from the production and supply of water which will never reach subscribers, and those caused by water loss reduction activities. This information can then be used to establish whether or not there is a point beyond which loss reduction is no longer effective in reducing the environmental impacts of drinking water supply. Results show that the improvement actions that start from a low water supply efficiency are clearly beneficial for ecosystems, human health and preservation of resources. When seeking to improve the efficiency beyond certain values (about 65%), the uncertainty makes it impossible to conclude for an environmental benefit on all impact categories. Graphical abstract: Highlights: Different action plans for loss reduction in drinking water networks are defined. Inventory of actions for each action plan is conducted and LCA impacts are computed. Impacts of action plan is compared with avoided impacts of drinking water production. Beyond an efficiency gain threshold, we can't conclude for an environmental benefit.